Calculation and Analysis of the Structure and Viscosity of B2O3-Regulated CaO-Al2O3-Based Mold Fluxes - Lifeng Chen; Kun Liu; Peng Han; Bin Yang; Lianghua Feng (Journal of Chemistry)
The high content of aluminum in the steel reacts with the CaO-Si2O-based mold fluxes, resulting in deterioration of the mold slag physical and chemical properties, which cannot be applied to the continuous casting molten slag casting process of high-Mn high-Al steel Herein, the thermodynamic and structural properties of low-reactivity CaO-Al2O3-based mold fluxes were investigated. The thermodynamic properties were studied based on the first principles of quantum mechanics. The results show that the formation of stable structures of B-O and O-B-O in the mold fluxes was beneficial to reduce the probability of structural interconnection, degree of polymerization, and viscosity of the molten slag. The increase in the ratio of CaO/Al2O3 = 0.88–2 led to an increase in the O2− concentration. O2− entered the [AlO4] structure to form a stable structure of [AlO6] and [AlO5], wherein [AlO6] was more stable than [AlO5], reducing the degree of polymerization of the network structure. When cosolvent content B2O3 = 2%–10%, a simple layered structure of [BO3] was formed, and the particle migration resistance, break temperature, and viscous activation energy of the mold fluxes were reduced, while the corrected optical basicity of mold fluxes was gradually increased.